Energy upcycle in anaerobic treatment: Ammonium, methane, and carbon dioxide reformation through a hybrid electrodeionization–solid oxide fuel cell system. (15th May 2017) - Xu, Linji; Dong, Feifei; Zhuang, Huichuan; He, Wei; Ni, Meng; Feng, Shien-Ping; Lee, Po-Heng
Graphical abstract: Highlights: EDI-SOFC integrated with AD is introduced for energy extraction from C and N pollutants. NH4 + dissociation to NH3 and H2 in EDI avoids C deposition in SOFC. EDI exhibits nutrient and heavy metal recovery. SOFCs display its adaptability with NH3, H2, and biogas. Energy balance ratio boosts from 1.11 to 1.75 by EDI-SOFC in a HK landfill plant. Abstract: To create possibilities for a more sustainable wastewater management, a novel system consisting of electrodeionization (EDI) and solid oxide fuel cells (SOFCs) is proposed in this study. This system is integrated with anaerobic digestion/landfills to capture energy from carbonaceous and nitrogenous pollutants. Both EDI and SOFCs showed good performances. EDI removed 95% and 76% ammonium-nitrogen (NH4 + -N) from diluted (0.025 M) to concentrated (0.5 M) synthetic ammonium wastewaters, respectively, accompanied by hydrogen production. SOFCs converted the recovered fuels, biogas mixtures of methane and carbon dioxide, to electricity. Under the optimal conditions of EDI (3.0 V applied voltage and 7.5 mm internal electrode distance (IED), and SOFCs (750 °C operating temperature), the system achieved 60% higher net energy output as compared to conventional systems. The estimated energy benefit of this proposed system showed that the net energy balance ratio is enhanced from 1.11 (existing system) to 1.75 (this study) for a local Hong Kong active landfill facility with 10.0 g L −1 chemical oxygen demand (COD) and 0.21 M NH4 + -N. Additionally, an average of 80% inorganic ions (heavy metals and nutrient elements) can be removed from the raw landfill leachate by EDI cell. The results are successful demonstrations of the upgrades of anaerobic processes for energy extraction from wastewater streams.